ANIMALISTIC GENRE IN ENGLISH AND UZBEK LITERATURE - Khalilova Eleonora (Zeta Repository, 2023)
The article deals with the disclosure of the essence of the genre of animalistics in the English-language Western and Uzbek literature. On the interaction of man with the environment, including the animal world